2022
DOI: 10.3390/jpm12030326
|View full text |Cite
|
Sign up to set email alerts
|

Stigma towards People with Mental Illness among Portuguese Nursing Students

Abstract: Stigma is a substantial obstacle when caring for people with mental illness. Nursing students’ negative attitudes towards people with mental illness may impact the quality of care delivered and consequentially patient outcomes. In this study, we assessed the stigmatising attitudes and beliefs of nursing students towards people with mental illness and examined its relationship with several psycho-socio-demographic variables. This was a quantitative, cross-sectional descriptive correlational study, which was dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
19
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
4
19
1
2
Order By: Relevance
“…For factor 2, the three items low loading may be highlighting complexity around country speci c and cultural differences in mental health beliefs and stereotypes [21]. Speci cally, that there are differences in sources of prejudice and beliefs around aetiology or causes of mental illness between young adults in rural Malawi [20] and Portugal [22,23] This may have affected the variability in the data and may explain the scattered results seen in the exploratory factor analysis. Indeed, focus group participants from our exploratory work on the MHLq's cultural relevance also questioned the high category scoring, particularly from the 'knowledge' subscale items.…”
Section: Discussionmentioning
confidence: 99%
“…For factor 2, the three items low loading may be highlighting complexity around country speci c and cultural differences in mental health beliefs and stereotypes [21]. Speci cally, that there are differences in sources of prejudice and beliefs around aetiology or causes of mental illness between young adults in rural Malawi [20] and Portugal [22,23] This may have affected the variability in the data and may explain the scattered results seen in the exploratory factor analysis. Indeed, focus group participants from our exploratory work on the MHLq's cultural relevance also questioned the high category scoring, particularly from the 'knowledge' subscale items.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the factors of stigma in order to improve stigma toward mental disorders in medical and nursing students. A study pointed out that fourth-year nursing students, who already had a clinical internship in the department of psychiatry, were less likely to show stigma than other nursing students [ 21 ]. A study found that women showed less stigmatization than men among medical students [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, exploring the perspectives towards people with schizophrenia among nursing students, as future nurses, will be invaluable in designing anti-stigma interventions for these students and ultimately improving the conditions of people with schizophrenia. Many quantitative studies have investigated nursing students’ knowledge of mental illness and/or their stigmatised attitudes and/or intentional behaviours towards people with mental illness [ 39 , 40 , 41 , 42 , 43 ]. Mental illness stigma is influenced by multiple factors [ 44 ], especially cultural factors [ 45 ].…”
Section: Introductionmentioning
confidence: 99%